Design And Development Of Android-Based Medical Dictionary Application - Wicak, Wahyu (LPPM of STIMIK ESQ, 2018)
The development of mobile phone needs is currently getting higher, so that it does not rule out the possibility for all people to use mobile phones, at this time mobile phones are growing with a variety of features that support them so that interesting applications can run on mobile phones. Even in the medical world requires an application, an application that makes it easy for doctors to use in the search for medical terms that are relatively complicated. In this research aims to help doctors who are still students and female students in terms of understanding in the medical term that is very complicated and very much. Various kinds of medical terms are approximately 30,000 medical terms which here I take just a few samples consisting of 50 words. In this study an application was made